Prevalence and characterization of forgoing care: comparison of two prospective multicentre cohorts between pre-COVID-19 era and a lockdown period - Delphine Douillet; Clémence Dupont; Noémie Leloup; Grégory Ménager; Maud Delori; Caroline Soulie; François Morin; Thomas Moumneh; Dominique Savary; Pierre-Marie Roy; Aurore Armand (BMC, 2022)
Abstract Background Little is known about patients who forego healthcare, although it is an important provider of unfavorable health-related outcomes. Forgoing healthcare characterizes situations in which people do not initiate or interrupt a care process, even though they perceive the need for it, whether or not this need is medically proven. The aims of this study were to assess the prevalence and the determinants of patients who forego healthcare. The second aim was to compare the characteristics of patients who gave up healthcare during the French lockdown due to COVID-19. Methods We conducted two multicenter cross-sectional studies in 2017 and 2020 carried out in French patients presenting to the emergency departments. Patients who gave their consent to participate were interviewed with a standardized questionnaire. It consisted of two parts: epidemiological characteristics and health care refusal. A third part concerning the renunciation of care during the COVID-19 period was added to the second study period. Results A total of 1878 patients had completed the questionnaire during the interview with the physicians, 900 during the first period in 2017 (47.9%) and 978 (52.1%) during the second period. A total of 401/1878 patients reported not seeking care in the last 12 months (21.4% [95%CI: 19.5-23.3%]). In 2020, patients forewent care more during the confinement period than outside with different characteristics of the foregoing care populations. Conclusion Forgoing care is common in a universal health care system such as France's and increased during the pandemic. Key public health messages targeted at the reasons for not seeking care must now be disseminated in order to combat this.